Predictors of Diabetes Self-Management among Type 2 Diabetes Patients - Azylina, Gunggu; Chang, Ching Thon; Cheah, W.L (Hindawi Publishing Corporation, 2016)
Diabetes mellitus is a public health concern in Malaysia. Treatment of diabetes is costly and can lead to complications if disease is poorly controlled. Diabetes self-management (DSM) is found to be essential for optimal glycemic control. This cross-sectional study was conducted among samples from four randomly selected diabetes clinics in Sarawak,Malaysia. The aim was to determine the predictors for DSM. Face-to-face interview using questionnaire was used to collect data. Four hundred respondents with type 2 diabetes mellitus (T2DM) were recruited. Majority of the respondents were Sarawak Bumiputra (Iban and Bidayuh, 48.6%) and female (68.6%). The mean age was 58.77 years (SD = 11.46) and approximately half of the respondents (50.6%) had T2DM for six years (SD = 4.46). The mean fasting blood glucose (FBG) was 8.06mmol/L (SD = 2.94), with majority (76.1%) having the level higher than 6.1mmol/L. Multiple logistic regression tests showed significant linear relationship between DSM and belief in treatment effectiveness (